2006
DOI: 10.1016/j.jmb.2006.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Probing Molecular Docking in a Charged Model Binding Site

Abstract: A model binding site was used to investigate charge-charge interactions in molecular docking. This simple site, a small (180A(3)) engineered cavity in cyctochrome c peroxidase (CCP), is negatively charged and completely buried from solvent, allowing us to explore the balance between electrostatic energy and ligand desolvation energy in a system where many of the common approximations in docking do not apply. A database with about 5300 molecules was docked into this cavity. Retrospective testing with known liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 74 publications
(144 reference statements)
4
82
0
Order By: Relevance
“…The W191G cavity of cytochrome c peroxidase is used as a model system for introducing small molecule oxidation in an artificially created cavity. Goodin et al [28][29][30][31][32][33] studied the binding modes of several small molecules of structural types XII~XVI to the cytochrome c peroxidase. They are listed in Table 8.…”
Section: Example 6: Various Ligands Of Cytochrome C Peroxidasementioning
confidence: 99%
See 1 more Smart Citation
“…The W191G cavity of cytochrome c peroxidase is used as a model system for introducing small molecule oxidation in an artificially created cavity. Goodin et al [28][29][30][31][32][33] studied the binding modes of several small molecules of structural types XII~XVI to the cytochrome c peroxidase. They are listed in Table 8.…”
Section: Example 6: Various Ligands Of Cytochrome C Peroxidasementioning
confidence: 99%
“…The binding position of N-NH 2 group of Compound 8-5 is significantly different from the other two. In the studies of Goodin et al [33] the binding modes of two phenol derivatives (structural type XVI) were also examined: phenol (8-22, 2AS3, green) and 3-fluorocatechol (8-23, 2AS4, gray). Figure 7f shows these two molecules after overlapping the two corresponding protein structures.…”
Section: Example 6: Various Ligands Of Cytochrome C Peroxidasementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The binding of 2-amino-5-methylthiazole (2a5mt) to the W191G cavity mutant of cytochrome c peroxidase from E. coli (W191G) has been characterized by X-ray crystallography [9][10][11][12] and isothermal titration calorimetry [12] experiments, as well as by computational techniques. [13,14] This system is an ideal test case to investigate the magnitude of the entropy penalty to the binding free energy due to changes in receptor flexibility. Ligand binding affects the flexibility of both the W191G cavity and 190-195 gating-loop regions, [10,14] which may induce full opening of the gating loop in the case of benzimidazole (bzi).…”
Section: Introductionmentioning
confidence: 99%
“…Water molecules present in the active site further complicate the problem because of their ability to act as Lewis bases and/or acids. Computational studies on a binding pocket in the engineered cavity of cytochrome c peroxidase [203], showed better docking results when a single conserved water was allowed to move. Crystallographers and computational chemists have been interested in the proper placement and optimization of polar protons for decades.…”
Section: Ionization and Tautomerizationmentioning
confidence: 99%